Case report: First experience with stimulating anterior thalamic nuclei in pharmacoresistant epilepsy in Kazakhstan - Abzalova, Veronika; Kauynbekova, Sholpan; Makhambaev, Gabit; Dmitriev, Alexander; Tuleubaev, Berik (Frontiers in Human Neuroscience, 2024)
Introduction Pharmacoresistant epilepsy is a multicomponent disease that can be successfully treated surgically if the surgical tactics are properly defined. We present the first case of stimulation of anterior thalamic nuclei in pharmacoresistant epilepsy in Kazakhstan. This will be a new opportunity for Kazakhstanis diagnosed with epilepsy to achieve stable epilepsy remission. Materials The patient was born in 2000. The first episode of tonic clonic seizures with loss of consciousness occurred in 2014. Repeatedly underwent therapeutic and diagnostic measures in the neurological department. The frequency of seizures increased in dynamics. The results of instrumental examination revealed the following morphological changes: Morphological changes: Focal cortical dysplasia (FCD) in the left cingulate gyrus, hypometabolism in the left thalamus and forehead, signs of hippocampal sclerosis on both sides. Electroencephalogram (EEG) shows activity in frontal areas on both sides, more on the right. Based on clinical and instrumental data according to the 2017 ILAE classification, the diagnosis was Structural focal frontal lobe epilepsy with bilateral tonic-clonic seizures. FСD of the left cingulate gyrus. Resistance to antiepileptic therapy. Methods The patient was hospitalized in the department of neurosurgery. In light of the evidence indicating structural changes in the brain substance and ambiguous EEG findings, the indications for deep brain stimulation (DBS) of the anterior nucleus (ANT) were made. Electrode implantation was performed under general anesthesia, and preoperative computer tomography (CT) scans were performed using the CRW® stereotactic system in combination with magnetic resonance imaging (MRI) scans using Brainlab Neuronavigation with 3D Atlas to identify the anterior thalamic nuclei. Conclusion The observed structural changes in the brain substance and the ambiguous EEG results call into question the efficacy of surgical procedures aimed at removing existing foci or destroying them. Based on the above, as well as the experience of foreign colleagues, the choice of neurosurgeons was DBS ANT. Although the selection of ideal candidates for thalamic stimulation is still controversial, in the described case we were able to achieve control of seizure activity. The patient was seizure free for 2 months after surgery. The patient was discharged on postoperative day 7.